Advances in Synthesis and Applications of Microalgal Nanoparticles for Wastewater Treatment - Prashant Agarwal; Ritika Gupta; Neeraj Agarwal (Journal of Nanotechnology)
Rapid industrialization, economic development, and population overgrowth are the major reasons responsible for the release of organic and inorganic substances into the environment, further leading to environmental pollution and contamination of water. Nowadays, it is truism that wastewater treatment has raised concern worldwide and is the need of the hour. Therefore, it is necessary to conserve sustainable energy and adopt advanced wastewater treatment technologies. Microalgae culture is gaining tremendous attention as it provides a combined benefit of treating wastewater as a growth medium and algae biomass production which can be used for several livestock purposes. Microalgae are ubiquitous and extremely diverse microorganisms which can accumulate toxic contaminants and heavy metals from wastewater, making them superior contender to become a powerful nanofactory. Furthermore, they are versatile, relatively convenient, and easy to handle, along with various other advantages such as synthesis can be performed at low temperature with greater energy efficiency, less toxicity, and low risk to the environment. Comparing with other organisms such as fungi, yeast, and bacteria, microalgae are equally important organisms in the synthesis of nanoparticles; therefore, the study of algae-mediated biosynthesis of nanometals can be taken towards a newer branch and it has been termed as phytonanotechnology. Here, an overview of recent advances in wastewater treatment processes through an amalgamation of nanoparticles and microalgae is provided.